The Mediating Role of Stress in the Relationship Between Attention to Threat Bias and Psychotic-Like Experiences Depends on Coping Strategies - Prochwicz, Katarzyna; Kłosowska, Joanna; Dembińska, Aleksandra (Frontiers in Psychiatry, 2020)
Aim: Recent studies have provided evidence that enhanced stress level is associated with the increase of psychotic symptoms in both clinical and non-clinical populations. It has also been demonstrated that cognitive biases contribute to psychotic experiences. However, it remains unclear whether the effect of cognitive biases and perceived stress on psychotic-like experiences (PLEs) is influenced by coping methods. In the present study we examined whether the relationship linking cognitive biases with PLEs is mediated by the level of stress and whether particular coping methods modify the relationship between stress and PLEs. Methods: The study sample consisted of 290 non-clinical subjects; study variables were assessed by questionnaires. Moderated mediation analyses were conducted. Results: Perceived stress was found to serve as a partial mediator in the relationship linking attention to threat and external attribution biases with psychotic-like experiences, suggesting that these cognitive biases may affect psychotic symptoms through increasing stress level. Also, moderated mediation analysis revealed that the indirect effect of attention to threat bias on psychotic-like experiences via perceived stress was stronger at higher levels of distraction seeking coping. Conclusions: The findings imply that both perceived stress and coping styles are important factors affecting the association between cognitive biases and psychotic-like experiences.